Safe Cities Safe And Without Violence For Women And Girls, Advances And Challenges Of The City Of Medellín, Colombia - Montoya Ruiz, Ana Milena; Correa Londoño, Angela María (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The following research article exposes the results of the exploratory study of the city of Medellin for the implementation of the program cities safe without violence against women and girls Safe Cities and related explanatory to understand the unsafe conditions of women in urban contexts. It takes a tour by the policies of the city of Medellin and the strategies implemented in the framework of Safe Cities worldwide to improve security in cities, to strengthen the strategies of public security for the achievement of gender equality in the territory.